Calcium transients regulate the apical emergence of basally located progenitors during Xenopus skin development - Neophytos Christodoulou; Paris A. Skourides (Nature Communications)
Abstract The integration of basally located progenitors into an existing epithelium, termed apical emergence, is crucial for the morphogenesis and homeostasis of epithelial tissues and organs. Using Xenopus as a model system, we explore the role of intracellular calcium in apical emergence during the development of mucociliary skin epithelium. Our findings reveal that calcium transients precede the apical emergence of Multiciliated cell (MCC) progenitors and are essential for their insertion into the overlying skin epithelium. Furthermore, we demonstrate that phospholipase C (PLC) activity is required for generating calcium transients, which regulate MCC apical emergence via Calmodulin. The PLC/Ca²⁺/Calmodulin axis is necessary for the function of the apical actin network by influencing its stability. Lastly, we show that intracellular calcium regulates apical emergence in distinct basal progenitors. This study advances our understanding of the molecular mechanisms governing apical emergence and highlights the importance of calcium in coordinating cytoskeletal dynamics during epithelial morphogenesis.